Aquinas's ethics : metaphysical foundations, moral theory, and theological context - DeYoung, Rebecca Konyndyk; McCluskey, Colleen, 1957-; Dyke, Christina van, 1972- (Notre Dame, Ind. : University of Notre Dame Press, 2009)
Links Aquinas's metaphysics and anthropology to his action theory and ethics to illuminate how the moral theory is built on foundations laid elsewhere. The authors emphasize the integration of concepts of virtue, natural law, and divine grace within Aquinas's ethics.--From publisher's description.
Pt. 1. Human nature -- 1. The metaphysics of human nature -- 2. Soul and body -- 3. Human capacities and the image of God -- Pt. 2. Human actions -- 4. Actions and ends -- 5. The moral appraisal of actions -- 6. Habits and freedom -- Pt. 3. Human flourishing -- 7. The virtues -- 8. Law and grace -- 9. Theologically transformed virtue and vice.
Includes bibliographical references (p. 190-236) and index.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Ethics, Medieval; Thomas (von Aquin); Leib-Seele-Problem.